The effects of artificial sweeteners on body weight, body fat, and energy intake: A meta-analysis of meta-analyses - Fatemeh Hamedi-Kalajahi; Sanaz Asemani; Kousalya Prabahar; Neda Jourabchi-Ghadim; Alireza Ostadrahimi (BioSocial Health Journal)
Introduction: Overweight and obesity are prevalent worldwide and hence it can be considered as a global epidemic. Artificial sweeteners (ASs) are suggested to decrease energy intake and prevent obesity, however, the results of meta-analyses are inconsistent. Therefore, this umbrella meta-analyses was conducted to resolve these discrepancies and offer definitive evidence on the impact of ASs on body weight (BW), body mass index (BMI), and energy intake. Methods: PubMed, Scopus, EMBASE, and Web of Science were systematically searched from inception up to March 2023. Meta-analyses studies investigating the effect/association of AS on/with BW, BMI, and energy intake were included. Random-effects model was used for performing a meta-analysis. Subgroup analyses were carried out based on various independent variables. The quality of the included meta-analyses was evaluated using the AMSTAR2 questionnaire. Results: In this umbrella review, 12 meta-analyses were included. The findings from the umbrella meta-analysis of interventional studies showed that AS consumption significantly reduced BW according to standardized mean difference (SMD) analysis (ES=-0.38; 95% CI: -0.56, -0.20, P≤0.001), but not when using the weighted mean difference (WMD) (ES=-0.45; 95% CI: -1.15, 0.24, P=0.20). Also, AS did not affect the energy intake (ES=-0.28; 95% CI: -1.15, 0.59, P=0.59) based on WMD. However, AS significantly reduced BMI (ES=-0.28; 95% CI: -0.40, -0.15, P≤0.001) based on WMD analysis. Conversely, the umbrella meta-analysis of observational studies found that consuming ASs was associated with a 61% augmented risk of obesity and overweight. (ES=1.61; 95% CI: 1.36,1.87, P≤0.001). Conclusion: Despite observational studies, interventional studies show the benefits of ASs consumption. Future studies should be conducted focusing on the dose, types, and formulations of ASs, and more importantly, short-term and long-term consumption of ASs.